La regulación del derecho a la información pública en México - Carlos Manuel Rosales García (Ius Humani. Jornal do direito, 2012)
This paper exposes the legal nature and the usefulness of the right to information, is special in the case of Mexico. So it will be a study of the right to public information, in order to understand its origin and utility; then analyze the establishment and evolution in Mexican positive and discover its use as a mechanism for transparent use of public resources and the accountability of the State authorities.